SPAIN AND LATIN AMERICA: IMPERIAL TRADITION AND CONTEMPORANEITY - Agnessa Avilova (Ибероамериканские тетради)
The Spanish version of the evolution of the Empire differed from “classic” British: here there was a prolonged rupture of economic and political ties with the mother country. But now Spain and Latin American countries are developing cooperation in several directions. Spain is one of the major foreign investors for this region.